Juvenile Dermatomyositis (JDM) Complicated by Thrombotic Thrombocytopenic Purpura (TTP) and Purtscher's Retinopathy Responsive to Rituximab: Case Report and Literature Review - Gullapalli, Keerthi; Goldzweig, Ofra; Nanda, Kabita; Chekka, Ravi; Berry, Shanail; Bukulmez, Hulya (Frontiers in Pediatrics, 2020)
Juvenile dermatomyositis (JDM) is a multisystem vasculopathy that infrequently presents with acute complications. We report here a case of 12-year-old girl with Juvenile Dermatomyositis (JDM) who developed Thrombotic Thrombocytopenic purpura (TTP) and Purtscher’s retinopathy. The diagnosis of JDM was based on her clinical presentation (fever, myalgia, proximal muscle weakness, characteristic skin rash and elevated muscle enzymes). Despite improvement of rash, fever and weakness with corticosteroids and intravenous Immunoglobulins (IVIG), the patient developed retinal infarcts, thrombocytopenia, hemolytic anemia, renal failure and pulmonary edema within one week of initial treatment. A clinical diagnosis of TTP and Purtscher’s retinopathy was made and her ADAMTS13 activity was found to be low. Regardless of aggressive treatment with pulse steroid therapy, IVIG, plasmapheresis along with multiple infusions of Fresh Frozen plasma (FFP), her condition deteriorated. In view of her worsening condition, she received one dose of Rituximab and within 48 hours, her hematological and retinal involvements dramatically improved. Rituximab was given at the same dose once weekly thereafter for 4 total doses. Her disease process was halted, and retinopathy improved gradually over three years of maintenance therapy with cyclosporine, methotrexate, and IVIG. This patient is by far the only patient reported to develop JDM , TTP, and retinopathy concurrently, and successfully managed with B cell depletion therapy using Rituximab. This report documents the association of TTP and Purtscher’s retinopathy with JDM, emphasizing that early recognition and prompt treatment with rituximab along with immunosuppressive therapy could be of potential benefit in controlling disease activity.